1998
DOI: 10.3177/jnsv.44.819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fasting Serum Insulin Levels among Japanese School-Age Children.

Abstract: SummaryWe examined the physical constitution, serum lipids, fasting serum insulin (IRI), food intake, and physical activity in 1,330 children in three age groups (6-7, 9-10, and 12-13) in Nagao village for the period 1994-1996. Serum total cholesterol (TC) and high-density lipoprotein cholesterol (HDL-C) levels were positively correlated, and HDL-C and TG were negatively correlated in all age groups. IRI was significantly higher among the elder children, and it was also higher in girls than in boys. IRI was po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
4
4
0
1
Order By: Relevance
“…The increase in post-OGTT insulin levels is consistent with previous findings in which patients became relatively resistant to insulin after the start of GH therapy [19]. Fasting insulin levels have been shown to increase with age [15]; therefore, the results obtained in this study reflected physiological changes. Previous studies demonstrated that bioactive IGF-I levels increased through decreases in IGF-binding protein in the presence of hyperinsulinemia [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in post-OGTT insulin levels is consistent with previous findings in which patients became relatively resistant to insulin after the start of GH therapy [19]. Fasting insulin levels have been shown to increase with age [15]; therefore, the results obtained in this study reflected physiological changes. Previous studies demonstrated that bioactive IGF-I levels increased through decreases in IGF-binding protein in the presence of hyperinsulinemia [20].…”
Section: Discussionsupporting
confidence: 91%
“…TC and LDL-C levels were slightly lower in female patients. Since TC levels normally increase with puberty [15], the degree of decrease in TC observed may have been attenuated by pubertal hormonal changes. In the low dose group, a significant increase was observed in HDL-C levels, whereas no significant decreases were noted in TC and LDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…17 Larger observational studies in children and adolescents have used self-reported physical activity to assess the relationship between exercise and fasting insulin. Low physical activity scores were associated with elevated fasting insulin in a study of 1300 Japanese children aged 6 -13 13 and insulin sensitivity, as measured by the homeostasis model (an index of insulin resistance based on fasting levels of insulin and glucose), was significantly greater in 62 male high school students who performed highly aerobic exercise compared to 114 less active boys. 15 The Cardiovascular Risk in Young Finns Study reported that 12, 15 and 18-y-olds with a consistently sedentary lifestyle over 6 y of follow-up had higher fasting serum insulin than those who remained physically active over the same period.…”
Section: Discussionmentioning
confidence: 99%
“…5,32 Only a single study has reported a positive relationship between doubly labelled water measured energy expenditure and insulin. 12 However, the relationship in this study disappeared when two outliers were excluded from the analysis of this relatively small sample.…”
Section: Discussionmentioning
confidence: 99%